2020
DOI: 10.1002/bse.2455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of critical constructs for measurement of sustainable supply chain practices in lean‐agile firms of Indian origin: A hybrid ISM‐ANP approach

Abstract: The purpose of this paper is to evaluate the critical criteria that are influencing the successful implementation of sustainable supply chain practices (SSCP) in the lean‐agile manufacturing firm. From the systematic literature review and field professionals' opinion, various criteria that are influencing sustainable supply chain were identified. Data were collected from 16 experts and analysed by an integrated approach of “interpretive structural modeling (ISM) and analytic network process (ANP).” ISM methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 96 publications
0
45
0
Order By: Relevance
“…The association and hierarchy of barriers have been explored via ISM. ISM could not identify the order of priority of these influencing variables, as it is not suitable to present the ranking of barriers by the same approach (Chang et al , 2013; Digalwar et al , 2020). Ranking of technology adoption barriers is performed using the ANP method.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The association and hierarchy of barriers have been explored via ISM. ISM could not identify the order of priority of these influencing variables, as it is not suitable to present the ranking of barriers by the same approach (Chang et al , 2013; Digalwar et al , 2020). Ranking of technology adoption barriers is performed using the ANP method.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Azevedo et al (2011b) used balanced scorecard model, Lockamy (2014) used Bayesian networks, and Norrman and Jansson (2004) used tree analysis, that is, fault and evolution. Carvalho, Cruz‐Machado, and Tavares (2012), Ng et al (2015) and Chiarini (2014) used VSM; Digalwar et al (2020) used ISM with ANP.…”
Section: Outcome Phasementioning
confidence: 99%
“…In addition, SC is facing various pressures from all stakeholders for sustainable business development (Chang, Tsai, & Huang, 2019). Leon and Calvo‐Amodio (2017); Rajeev, Pati, Padhi, and Govindan (2017) and Digalwar et al (2020) suggested that SC should include the dimension of social and environmental performance measures into the conventional performance metrics. In addition to that, Luthra, Garg, and Haleem (2016); Orazalin (2020); Ciccullo, Pero, Caridi, Gosling, and Purvis (2018) and Zhan, Tan, Ji, and Tseng (2018) discussed the relevance of sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Digalwar et al [14] have evaluated the critical constructs for measuring sustainable SC practices in the case of Indian lean-agile firms. The authors found that technology-related constructs like "Information technologyenabled system support (ITS)" is the most significant construct which is in line with the present study too.…”
Section: Resultsmentioning
confidence: 99%